Трехфазный трехуровневый активный выпрямитель с гистерезисной системой автоматического управления - Плахтий, Александр Андреевич (НТУ "ХПИ", 2014)
В статье представлен анализ трёхуровневой активного выпрямителя с коррекцией коэффициента мощности. Трехуровневый активный выпрямитель компенсирует высшие гармонические составляющие, генерируемые нелинейными нагрузками, и реализуют коэффициент мощности близкий к единице.

Three phase diode bridge rectifiers have a low power factor. They are a powerful source of higher current harmonics in industrial network. Pressing issue is improvement of electromagnetic compatibility of three-phase rectifier units. One of the ways of power factor correction is the application of two-level active rectifiers. Two-level active rectifiers’ implements sinusoidal input phase currents and unity power factor. Another advantage of this rectifier is the implementation of the energy recovery from DC line to the three-phase network. Significant disadvantage of two-level active rectifier is high load requirements keys schemes. This leads to restrictions on the use of this scheme with the networks of medium and high voltage. One way to reduce the load requirements of the keys is to implement a three-level active rectifiers. The aim of this thesis is presentation of analysis of the automatic control system of three-level active three-phase rectifier, analysis of implemented power factor, analysis of quality of the input and output currents and voltages. Serial connection of IGBT-keys and output capacitors in a three-level active rectifier allows implementing minimal applied voltage to the circuit elements. This allows the use of a three-level active rectifier in medium voltage networks 1-35 kV. Besides multilevel structure allows to implement lower harmonic distortion of phase current in comparison with two-level rectifier.
Multilevel active three phase rectifier
Keywords: коэффициент мощности; коррекция; совместимость электромагнитная; active three-phase rectifier; power factor correction; electromagnetic compatibility